Framing of Salman Taseer assassination and Mumtaz Qadri execution in English leading press of Pakistan - asif, sadaf; zulfiqar, amna; waheed, anbreen (Journal of Peace, Development and Communication, 2021)
The study scrutinized the framing of blasphemy Case of Salman Taseer and Mumtaz Qadri by leading English press of Pakistan. The study discovered the editorial policies of English newspapers of Pakistan, on framing the issue through during the selected timeline. For evaluating relevant content of the news, purposive methods of sampling have been used. The study explored the framing of execution of Mumtaz Qadri and reaction of different political and religious groups to his execution in selected newspapers. It also investigates all prospect of framing theory that were closer to the study and which questions about how different editorial policies were used to frame the selected issue. To analyzing the content five frames; Attribution of having Responsibility frame, public Interest frame, Clash frame, Morality frame, and Harmony frame were constructed respectively.